2016
DOI: 10.18540/2446941602032016132
|View full text |Cite
|
Sign up to set email alerts
|

ISOTERMAS DE ADSORÇÃO DE ÍONS CÁLCIO (Ca+2) EM MATERIAIS CELULÓSICOS

Abstract: RESUMO: A água a ser utilizada em processos industriais demanda um tratamento e qualidade diferenciados. O objetivo desse estudo foi investigar o uso de três materiais celulósicos para abrandamento da água, sendo duas celuloses microcristalinas com granulometrias diferentes (CMC101 e CMC500) e a polpa Kraft de Eucalyptus branqueada. Realizou-se um estudo cinético para a obtenção de parâmetros otimizados, e determinaram-se isotermas de adsorção, utilizando diferentes concentrações de cálcio e assumindo três dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After 30 minutes we have the equilibrium process, then it is suggested that the calcium ion adsorption involved more than one process ( Juang et al 2002). Silva et al (2016) studied the adsorption of Ca 2þ ions in lignocellulosic material, and the results of the kinetic study showed that the pseudo-second-order model was better fitted to the experimental data.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 minutes we have the equilibrium process, then it is suggested that the calcium ion adsorption involved more than one process ( Juang et al 2002). Silva et al (2016) studied the adsorption of Ca 2þ ions in lignocellulosic material, and the results of the kinetic study showed that the pseudo-second-order model was better fitted to the experimental data.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Regarding water hardness, the Brazilian Ministry of Health establishes for potable water standards the maximum permissible value of 500 mg/L for the sum of calcium and magnesium concentrations. Generally, when water contains less than 50 mg/L of CaCO 3 , it is considered as soft, up to 150 mg/L is classified as semi-hard, with less than 300 mg/L is labeled as hard and when it presents values above 300 mg/L it is classified as very hard (Brasil 2006;Silva et al 2016). As a comparison, in European countries, such as Portugal, which use the 150-500 mg/L range as a reference value for total hardness.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%